Adherence to guidelines: an audit of the endoscopic management of acute upper non-variceal gastrointestinal bleeding - Hasmoni, Mohamed Hadzri; Che Aun, Azlida; Jaafar, Khairul Azhar; Poh, Tee Hoi (IIUM Medical Journal Malaysia, 2016)
Introduction: For patients with acute upper non-variceal gastrointestinal bleeding (AUNVB), various guidelines and meta-analysis have shown that combination endoscopic treatment is superior to a single treatment modality (injection or thermal coagulation) as an endoscopic haemostatic technique. This study aim to assess the adherence to ‘best practice’ standards (an emphasis on endoscopic treatment modalities) for patients with non-variceal upper gastrointestinal bleeding with high risk stigmata on endoscopic findings. Methods: Between January 2015 and March 2016, consecutive charts of patients hospitalized for acute upper gastrointestinal bleeding in Hospital Tengku Ampuan Afzan, Kuantan were reviewed. Data regarding initial presentation, endoscopic findings and management were collected. The inclusion criteria were patients with peptic ulcer disease and high risk stigmata on endoscopic findings. Results: Eighty one patients were included in the final analysis. There were 62 males and 19 females patients with mean age of 62.5 ± 1.5. Although the statistical analysis was not significant, more than half of the patients (60.5%) were given a single treatment modality to achieve haemostasis. Only 33.3% and 6.2% patients received a combination of two and three treatment modalities respectively. Conclusions: There was marked variability between the process of care and ‘best practice’ in AUNVB. Certain patient and situational characteristics may influence guideline adherence. Further studies are needed to delineate the underlying causes.